Globally robust stability analysis for stochastic Cohen – Grossberg neural networks with impulse control and time-varying delays - Guo, Y. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
By constructing suitable Lyapunov functionals, in combination with the matrix-inequality technique, a new simple sufficientlinear matrix inequality condition is established for the globally robustly asymptotic stability of the stochastic Cohen –Grossberg neural networks with impulsive control and time-varying delays. This condition contains and improves someprevious results from the earlier references.